VD_FINDINFO Décision / 2013 / 743 vom 5. September 2012 - VD Tribunal cantonal (2012)
EXÉCUTION ANTICIPÉE DE LA PEINE, DÉTENTION PRÉVENTIVE, COMPÉTENCE RATIONE MATERIAE | 228 CPP (CH), 230 CPP (CH), 236 CPP (CH)